Comparative Analysis of the Microbiota Between Sheep Rumen and Rabbit Cecum Provides New Insight Into Their Differential Methane Production - Mi, Lan; Yang, Bin; Hu, Xialu; Luo, Yang; Liu, Jianxin; Yu, Zhongtang; Wang, Jiakun (Frontiers in Microbiology, 2018)
The rumen and the hindgut represent two different fermentation organs in herbivorous mammals, with the former producing much more methane than the latter. The objective of this study was to elucidate the microbial underpinning of such differential methane outputs between these two digestive organs. Methane production was measured from 5 adult sheep and 15 adult rabbits, both of which were placed in open-circuit respiratory chambers and fed the same diet (alfalfa hay). The sheep produced more methane than the rabbits per unit of metabolic body weight, digestible neutral detergent fiber, and acid detergent fiber. pH in the sheep rumen was more than 1 unit higher than that in the rabbit cecum. The acetate to propionate ratio in the rabbit cecum was more than 3-fold greater than that in the sheep rumen. Comparative analysis of 16S rRNA gene amplicon libraries revealed distinct microbiota between the rumen of sheep and the cecum of rabbits. Hydrogen-producing fibrolytic bacteria, especially Butyrivibrio, Succiniclastium, Mogibacterium, Prevotella, and Christensenellaceae, were more predominant in the sheep rumen, whereas non-hydrogen producing fibrolytic bacteria, such as Bacteroides, were more predominant in the rabbit cecum. The rabbit cecum had a greater predominance of acetogens, such as those in the genus Blautia, order Clostridiales, and family Ruminococcaceae. The differences in the occurrence of hydrogen-metabolizing bacteria probably explain much of the differential methane outputs from the rumen and the cecum. Future research using metatranscriptomics and metabolomics shall help confirm this premise and understand the factors that shape the differential microbiota between the two digestive organs. Furthermore, our present study strongly suggests the presence of new fibrolytic bacteria in the rabbit cecum, which may explain the stronger fibrolytic activities therein.